Plant- and stimulus-specific variations in remote-controlled sieve-tube occlusion - Furch, Alexandra CU (Landes Bioscience, 2008)
Phloem injury triggers local sieve-plate occlusion including callose-mediated constriction and protein plugging of sieve pores. In intact plants, reversible sieve-plate occlusion is induced by electric potential waves (EPWs)—accompanied by Ca(2+)-influx—as result of distant burning. Here, we present additional results which pertain to (a) the variability of EPW-profiles in relation to forisome conformation in intact Vicia faba plants and (b) the differential occlusion reactions to burning and cutting in various plant species. A correlation between stimulus perception and mode of phloem loading is discussed.